IMPORTANCE OF ANDRAGOGIC APPROACH IN LANGUAGE EDUCATION - Alimova Madina (Galaxy International Interdisciplinary Research Journal, 2023)
At the moment, an employee who is in accordance with the requirements of the Times should have a culture of communication, as well as knowledge of foreign languages, in addition to excellent knowledge of his profession. For this reason, there is a need to learn a foreign language in the adult layer. The article provides views on the importance of the andragogic approach to language education.